Insight of anode reaction for CWS (coal water slurry) electrolysis for hydrogen production. (1st February 2016) - Ge, Lan; Gong, Xuzhong; Wang, Zhi; Zhao, Lixin; Wang, Yuhua; Wang, Mingyong
Abstract: Mechanism ofCWS (coal water slurry) electrolysis was investigated by using anode reaction kinetics. The results indicated that the activation energies of electrode reaction reduce with the increase in activity of carbon materials. According to the electrode reaction kinetics, the direct oxidation ofCWS electrolysis occurred easily under lower concentration of electrolyte and higher concentration ofCWS . On the contrary, the indirect oxidation ofCWS electrolysis took place. Because of the high oxygen evolution potential of water electrolysis in H2 SO4 solution (1.23 V), the direct oxidation ofCWS electrolysis mainly occurred under water decomposition potential (0.5–1.23 V). As NaOH solution was used as electrolyte, it was difficult to distinguish direct and indirect oxidation under the low potential (0.4 V). With increasing stirring rate, the electrode reaction activation energies ofGWS (graphite water slurry) electrolysis increased slightly and were always lower than 40 kJ/mol. The results indicated thatGWS electrolysis was controlled by diffusion and the increase in stirring rate could not reduce the polarization. Highlights: The reactivity of CWS electrolysis depended on the coal activity. The direct oxidation occurred easily at low electrolyte concentration. The direct oxidation in H2 SO4 occurred under water decomposition potential. It is difficult to distinguish between direct and indirect oxidation in NaOH. Ultrasonic could reduce concentration polarization at low potential.